A survey of medical plants of Cyrene (campus Apollo) Shahat-Al-Jabal Al-Akhdar, Libya. - Ali, Rania F.; AL-Sunosy, Hamida M.; Saed, Enas M. (Libyan Journal of Science &Technology, 2025)
AL-Jabal AL-Akhdar region is very rich in diversity in plants, and studies are still few in AL-Jabal AL-Akhdar. This study was 2021/2022, conducted for four seasons. An inventory of the plants of this region was made entirely, and the medicinal plants were counted in the study area. The results indicated the presence of a total of 70 medicinal plant species belonging to 45 families and 67 genera and 68 species. Gymnosperms were represented by only 3 families, 3 genera, and 3 species, 1 sup species. Angiosperms composed the most dominant botanical group with 41 families. Dicotyledons were the most presented group of the angiosperms with 35 families, 7 genera and 58 species, and 1 sup species, whereas Monocotyledons comprised a far less diverse group of medicinal plants in the area study with only 6 families, 7 genera and 7 sup species, pteridophyta, 1 family, 1 genus,1 species. Asteraceae and Lamiaceae attained the highest number of genera recorded in the study area with 5 genera and 5 species, followed by Fabaceae with 4 genera, 5 genera and 5 species, followed by Fabaceae with 4 genera and 4 species. Our results revealed that the most represented life forms of the medicinal plants in Shahat were Therophytes (Th) (36%) 24 species, Phanerophytes (Ph) (18%) 12 species, Chamaephytes (Ch) (16%) 11 species, followed by Geophytes (G) (10%) 7 species, Heleophytes (H) and Nano-phanerophytes (7%) 5 species, as for Hemicryptophytes, Hydrophytes and Linaes the percentage of their presence was very simple (2%), It is represented by one type for each of them. Also on the list is an endemic and endangered medicinal plant. Cyclamen rohlfsianum Aschers, belonging to the family Primulaceae.